The Pain Assessment in Impaired Cognition scale (PAIC15): A multidisciplinary and international approach to develop and test a meta‐tool for pain assessment in impaired cognition, especially dementia. (13th October 2019) - Kunz, Miriam; de Waal, Margot W. M.; Achterberg, Wilco P.; Gimenez‐Llort, Lydia; Lobbezoo, Frank; Sampson, Elisabeth L.; van Dalen‐Kok, Annelore H.; Defrin, Ruth; Invitto, Sara; Konstantinovic, Ljubica; Oosterman, Joukje; Petrini, Laura; et al.
Abstract: Background: Over the last decades, a considerable number of observational scales have been developed to assess pain in persons with dementia. The time seems ripe now to build on the knowledge and expertize implemented in these scales to form an improved, "best‐of" meta‐tool. The EU‐COST initiative "Pain in impaired cognition, especially dementia" aimed to do this by selecting items out of existing observational scales and critically re‐assessing their suitability to detect pain in dementia. This paper reports on the final phase of this collaborative task. Methods: Items from existing observational pain scales were tested for "frequency of occurrence (item difficulty), " "reliability" and "validity." This psychometric testing was carried out in eight countries, in different healthcare settings, and included clinical as well as experimental pain conditions. Results: Across all studies, 587 persons with dementia, 27 individuals with intellectual disability, 12 Huntington's disease patients and 59 cognitively healthy controls were observed during rest and movement situations or while receiving experimental pressure pain, respectively. The psychometric outcomes for each item across the different studies were evaluated within an international and multidisciplinary team of experts and led a final selection of 15 items (5x facial expressions, 5x body movements, 5x vocalizations). Conclusions: The final list of 15 observational items have demonstrated psychometric quality and clinical usefulness both in their former scales and in the present international evaluation; accordingly, they qualified twice to form a new internationally agreed‐on meta‐tool for Pain Assessment in Impaired Cognition, the PAIC‐15 scale. Significance: Using a meta‐tool approach by building on previous observational pain assessment scales and putting the items of these scales through rigorous empirical testing (using experimental as well as clinical pain studies in several European countries), we were able to identify the best items for pain assessment in individuals with impaired cognition. These selected items form the novel PAIC15 scale (pain assessment in impaired cognition, 15 items).